The Minnesota mobile extracorporeal cardiopulmonary resuscitation consortium for treatment of out-of-hospital refractory ventricular fibrillation: Program description, performance, and outcomes. (December 2020) - Bartos, Jason A.; Frascone, R.J.; Conterato, Marc; Wesley, Keith; Lick, Charles; Sipprell, Kevin; Vuljaj, Nik; Burnett, Aaron; Peterson, Bjorn K; Simpson, Nicholas; Ham, Kealy; Bruen, Charles; et al.
Abstract: Background: We describe implementation, evaluate performance, and report outcomes from the first program serving an entire metropolitan area designed to rapidly deliver extracorporeal membrane oxygenation (ECMO)-facilitated resuscitation to patients with refractory ventricular fibrillation/ventricular tachycardia (VF/VT) out-of-hospital cardiac arrest (OHCA). Methods: This observational cohort study analyzed consecutive patients prospectively enrolled in the Minnesota Mobile Resuscitation Consortium's ECMO-facilitated resuscitation program. Entry criteria included: 1) adults (aged 18–75), 2) VF/VT OHCA, 3) no return of spontaneous circulation following 3 shocks, 4) automated cardiopulmonary resuscitation with a Lund University Cardiac Arrest System (LUCAS™), and 5) estimated transfer time of < 30 min. The primary endpoint was functionally favorable survival to hospital discharge with Cerebral Performance Category (CPC) 1 or 2. Secondary endpoints included 3-month functionally favorable survival, program benchmarks, ECMO cannulation rate, and safety. Essential program components included emergency medical services, 3 community ECMO Initiation Hospitals with emergency department ECMO cannulation sites and 24/7 cardiac catheterization laboratories, a 24/7 mobile ECMO cannulation team, and a single, centralized ECMO intensive care unit. Findings: From December 1, 2019 to April 1, 2020, 63 consecutive patients were transported and 58 (97%) met criteria and were treated by the mobile ECMO service. Mean age was 57 ± 1.8 years; 46/58 (79%) were male. Program benchmarks were variably met, 100% of patients were successfully cannulated, and no safety issues were identified. Of the 58 patients, 25/58 (43% [CI:31–56%]) were both discharged from the hospital and alive at 3 months with CPC 1 or 2. Interpretation: This first, community-wide ECMO-facilitated resuscitation program in the US demonstrated 100% successful cannulation, 43% functionally favorable survival rates at hospital discharge and 3 months, as well as safety. The program provides a potential model of this approach for other communities. Funding: The Helmsley Charitable Trust